Do Spanish–English Bilinguals have Their Fingers in Two Pies – or is It Their Toes? An Electrophysiological Investigation of Semantic Access in Bilinguals - Hoshino, Noriko; Thierry, Guillaume (Frontiers in Psychology, 2012)
We examined the time course of cross-language activation during word recognition in the context of semantic priming with interlingual homographs. Spanish-English bilinguals were presented pairs of English words visually one word at a time and judged whether the two words were related in meaning while recording event-related potentials (ERPs). Interlingual homographs (e.g., “pie”) appeared in the target position and were preceded by primes that were either related to the English meaning (e.g., “apple”), related to the Spanish meaning of interlingual homographs (e.g., “toe”) or totally unrelated (e.g., “floor”/“bed”). Spanish-English bilinguals showed semantic priming not only when interlingual homographs were related to the English meaning but also to the Spanish meaning of the prime. These priming effects were detectable in the mean amplitude of the N400 (350-500 ms) even when the target word was related to the prime in Spanish and the context of the experiment was English. However, the relatedness effect survived into the window of a late positive component, LPC (550-700 ms) only for stimulus pairs related in English. To verify that the observed pattern of the results was due to participants’ bilingualism, we also tested a group of English monolinguals. The monolinguals showed a semantic priming effect for the N400 and LPC time windows only when interlingual homographs were related to the English meaning. These results suggest that both languages are activated in the classical time frame of semantic activation indexed by N400 modulations, but that semantic activation in the non-target language is subsequently inhibited.